The boy who owned the school : a comedy of love - Paulsen, Gary. (New York : Orchard Books, 1990)
Jacob Freisten, often in a fog, tries to ease through high school unnoticed; but a beautiful classmate takes notice of him and his life begins to change.
School Library Journal.
Booklist.
Horn Book.
7.3
Young Adult
Keywords: High schools -- Fiction; Schools -- Fiction; High schools -- Fiction; School stories; High schools -- Fiction; Schools -- Fiction